ZnTe-based UV sensors - Pavelets, S.Yu.; Bobrenko, Yu.N.; Semikina, T.V.; Sheremetova, G.I.; Atdaiev, В.S.; Krulikovska, K.B.; Mazin, M.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
A р-ZnTe/n-CdSe heterojunction was used for making polycrystalline ZnTebased UV sensors. The heteropair components have the same crystal structure and close lattice parameters. ZnTe and CdSe were grown using thermal evaporation and quasiclosed space condensation. A transparent current collecting electrode for the surfacebarrier structure of р-ZnTe/n-CdSe heterojunction was made of degenerate p-Cu₁.₈S. Surface relief of ZnTe grown on different substrates was studied with scanning atomic force microscopy. The energy band offset diagrams of heterojunction are built and photosensitivity spectra are presented.